36PResults of a first panTRK IHC ringtrial. (7th November 2019) - De Winne, K; Sorber, L; Lambin, S; Keulen, L; Broeckx, G; Pauwels, P; Zwaenepoel, K
Abstract: Background: Because of the limited experience with tyrosine kinase receptor (TRK) gene fusion, a Belgian ring trial for TRK immunohistochemistry (IHC) staining was organised by the pathology department of Antwerp University Hospital. The trial was conducted between January and July 2019 with a total of 9 participating laboratories and aimed to harmonize pan-TRK IHC staining protocols and pan-TRK IHC interpretation. Methods: The first and last slides of six selected cases were stained for TRK using the VENTANA pan-TRK Assay (clone EPR17341) on the Benchmark Ultra platform. Each participating laboratory received two unstained slides and was asked to return one TRK–stained slide per case and to report the protocol used and their interpretation. One site participated with two different protocols. The stained slides were evaluated by two designated pathologists. The results of a comparative study evaluating the IHC interpretations from the in-house pathologists of the different laboratories and those obtained from the trial-designated pathologists were communicated to the participating laboratories. Results: Two different clones were used during the ring trial: A7H6R (Cell Signaling) and EPR17341 (Abcam/Ventana). The VENTANA pan-TRK Assay (clone EPR17341) on the Benchmark Ultra platform was most popular and used by 40% of the labs. The remaining in-house protocols used EPR17341 in its concentrated form (abcam) or A7H6R (Cell Signaling). Overall, 7 protocols achieved a sufficient performance mark and 3 labs were advised to further optimise the protocol. Interpretation of panTRK IHC proofed to be challenging in cases with physiological TRK expression. In addition, depending on the NTRK fusion partner, the staining can vary strongly in both intensity and staining pattern. Conclusions: To our knowledge, this is the first panTRK IHC ring trial. According to our results, the EPR17341 and A7H6R clones are both highly recommendable antibodies for panTRK IHC. Labs using the Ventana ready-to-use system based on the EPR17341 clone and using the recommended protocol settings scored best. However, given some small optimisation, all labs scored well on the technical staining and the succeeding evaluation. Legal entity responsible for the study: Antwerp University Hospital. Funding: Bayer. Disclosure: All authors have declared no conflicts of interest.